Antecedents of Organizational Citizenship Behavior - Noor Arifin; Emilia Inta Argadea; Eko Nur Fu'ad (Journal of Management and Entrepreneurship Research, 2021)
Objective: This study aims to analyze the effect of transformational leadership, self-efficacy, and work loyalty on organizational citizenship behavior. Research Design & Methods: This study is explanatory research using a quantitative approach. The research sample was selected based on the proportional random sampling method from employees of one of the furniture companies in Jepara with a total of 89 people. Primary data was obtained using a questionnaire that was distributed to employees directly. Statistical data analysis was performed using multiple linear regression with SPSS tool. Findings: Empirically, the results of this study accept all the hypotheses proposed, that: transformational leadership style has a significant effect on organizational citizenship behavior; self-efficacy has been proven to have a significant effect on organizational citizenship behavior; and work loyalty proved to have a significant effect on organizational citizenship behavior. Implications & Recommendations: The results of this study support previous research and contribute to a literature study that emphasizes the issue of this research in the context of a company experiencing a decline in performance so that it requires an extra employee role (OCB). Contribution & Value Added: Based on the dominant variable analysis, the company can increase the extra role of employees by increasing employee loyalty. And then loyalty can be spurred by directing employees to work in teams.